Research on the Implementation of Recursive Algorithm Based on C Language - Zhu, Zhigang; Sun, Wei (Journal of physics. Conference series, 2021)
In the utilization of C language, it often appears that the function calls itself directly or indirectly, that is, the function calls itself recursively. The recursive solution of the same kind of problem can be expressed by recursion, and the specific problem can be reduced by recursion. Based on this, this paper first analyses the concept and function of C language recursion, then studies the process description of recursion algorithm, and finally gives the implementation strategy of C language recursion algorithm.